Incident cervical HPV infections in young women: Transition probabilities for CIN and infection clearance (2011)
Background: We describe transition probabilities for incident human papillomavirus (HPV) 16/18/31/33/35/45/52/58/59 infections and cervical intraepithelial neoplasia (CIN) 1 lesions. Methods: Women ages 16 to 23 years underwent cytology and cervical swab PCR testing for HPV at approximately 6-month intervals for up to 4 years in the placebo arm of an HPV vaccine trial. The cumulative proportion of incident HPV infections with diagnosed CIN, clearing (infection undetectable), or persisting without CIN, were estimated. Results: Most incident infections cleared, without detection of CIN, ranging at 36 months from 66.9% for HPV31 to 91.1% for HPV59. There was little variation in the 36-month proportion of incident HPV16, 18, and 31 infections followed by a CIN1 lesion positive for the relevant HPV type (range 16.7%-18.6%), with lower risks for HPV59 (6.4%) and HPV33 (2.9%). Thirty-six-month transition probabilities for CIN2 ranged across types from 2.2% to 9.1%; however, the number of events was generally too small for statistically significant differences to be seen across types for this endpoint, or CIN3. Conclusions: Some incident HPV types appear more likely to result in diagnosed CIN1 than others. The relative predominance of HPV16, vis-à-vis some other high-risk HPV types (e.g., HPV33) in prevalent CIN2/3, appears more directly associated with relatively greater frequency of incident HPV16 infections within the population, than a higher risk of infection progression to CIN2/3. Impact: Nearly all incident HPV infections either manifest as detectable CIN or become undetectable within 36 months. Some HPV types (e.g., 16 and 33) appear to have similar risk of CIN2/3 despite widely varied incidence. ©2011 AACR.